THE USE OF ARTIFICIAL INTELLIGENCE TOOLS IN BUSINESS - Marcon, Margarete de Fátima; Bet, Yago Marcon; Rojo, Cláudio Antonio; Parcianello, Roberta Vanessa Rojo (Seven Editora, 2025)
Artificial Intelligence (AI) research has emerged as a crucial field of study, with the potential to transform the industry and society. This article explores the evolution of AI in the business context, through a systematic review of the literature, to understand the impact of this technology on business. The objective is to trace the trajectory of AI, highlighting its main applications, benefits, and challenges. The rationale for the study lies in the need to understand how AI has been integrated into companies and what its implications are for the corporate future. The systematic review of the literature was chosen as a methodology to ensure a comprehensive and critical analysis of existing studies. This qualitative approach involved the rigorous definition of inclusion and exclusion criteria, with the selection of peer-reviewed articles and high-quality studies. The research identified the key phases of AI's evolution, from its earliest implementations to the most recent innovations. The results show that AI has been applied in areas such as process automation, data analysis, and customer service, offering significant advantages such as greater efficiency and personalization. However, challenges also arise, including governance issues and resistance to change. In conclusion, AI is shaping the corporate environment in a profound and diverse way. While it offers innovative solutions and drives business success, it is critical for businesses to address the challenges associated with their implementation. Adopting a well-defined strategy and addressing the complexities of AI are essential to maximizing its benefits and sustaining future innovation. The study underlines the importance of effective AI integration to drive business growth and transformation.DOI: https://doi.org/10.56238/sevened2024.037-169